2022
DOI: 10.1039/d0cs00535e
|View full text |Cite
|
Sign up to set email alerts
|

Beyond classical sulfone chemistry: metal- and photocatalytic approaches for C–S bond functionalization of sulfones

Abstract: Sulfones are excellent candidates for the design of new C–C and C–X bond-forming reactions owing to the easy activation of C–S bonds. This review focuses on challenges and recent opportunities for catalytic functionalization of sulfones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 302 publications
0
25
0
Order By: Relevance
“… , In addition, the sulfone moiety is an important synthetic target and widely used as a versatile synthetic intermediate for organic chemistry. Therefore, many synthetic methodologies have been developed for the preparation of sulfones, for example, oxidation of sulfides, Friedel-Crafts-type sulfonation with sulfonyl halides, and coupling of sulfinic acid salts. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… , In addition, the sulfone moiety is an important synthetic target and widely used as a versatile synthetic intermediate for organic chemistry. Therefore, many synthetic methodologies have been developed for the preparation of sulfones, for example, oxidation of sulfides, Friedel-Crafts-type sulfonation with sulfonyl halides, and coupling of sulfinic acid salts. …”
Section: Introductionmentioning
confidence: 99%
“…3 CN/ H 2 O as mixed solvents, carbon electrode as the anode, platinum electrode as the cathode, and a constant current of 15 mA (…”
mentioning
confidence: 99%
“…To achieve this, we envisioned that an appropriate base metal catalyst can be exploited to activate the aromatic reaction partner, in order to promote efficient desulfonylative CÀ C cross-coupling with the sulfone. A potential complication that may arise is the site selectivity of sulfone activation, since transition metals are known to insert into C(sp 2 )À S bonds within aryl/alkenyl sulfones [35][36][37] leading to undesired products. Herein, we disclose a series of versatile Fe-or Nicatalyzed transformations that address the aforementioned challenges (Scheme 2b).…”
Section: Introductionmentioning
confidence: 99%
“…1a) (Buynak et al 2000; Sravya et al 2019;Sravya et al 2016). Moreover, allylic sulfones can also serve as a kind of versatile building block to construct many complex organic molecules (Corpas et al 2022;Nambo et al 2022). Owning to their precious applications, tremendous efforts have been devoted to the exploration of e cient synthetic methods for allylic sulfones all along (Chu et and Zi (Zhang et al 2020) reported palladium-catalysed hydrosulfonylation of 1,3-dienes with sulfonyl hydrazides and sul nic acid respectively (Fig.…”
Section: Introductionmentioning
confidence: 99%